Prevalence of tissue BRCA gene mutation in ovarian, fallopian tube, and primary peritoneal cancers: A multi-institutional study - Arb Aroon Lertkhachonsuk (2020)
© 2020 Asian Pacific Organization for Cancer Prevention. Background and objective: Ovarian, fallopian tube, or primary peritoneal cancer patients with BRCA gene mutation have enhanced sensitivity to platinum-based regimens and PARP inhibitors. However, the knowledge regarding BRCA mutation in Thai patients is limited. This study aimed at identifying the prevalence and characteristics of somatic and germline BRCA 1 and 2 mutations in Thai patients with these cancers. Materials and Methods: The paraffin blocks of tumors with histology of high grade serous, high grade endometrioid, or clear cell carcinoma obtained between June 2016 and December 2017 were analyzedto evaluate BRCA mutation using next-generation sequencing system. Blood or normal tissue paraffin blocks of positive patients were further tested for germline BRCA mutation. Results: Tissue paraffin blocks of 178 patients were collected but only 139 were analyzed. Positive BRCA mutation was identified in 24 patients (17.3%): BRCA1 in 13 cases, BRCA2 in 10 cases, and BRCA1 and 2 in the rest one. Germline mutation study in blood or normal tissue in 23 positive patients revealed BRCA mutation in 14 cases, BRCA1 in 8 cases and BRCA 2 in 6 cases. Overall, the prevalence of somatic and germline mutation was 6.5% (9 out of 138 patients) and 8.7% (14 out of 138 patients), respectively. The most common histology associated with BRCA mutation was high grade serous cancer (27.3%). No significant difference was found between patients with or without BRCA mutation in terms of stage, outcome, platinum status, and survival outcome. Conclusion: BRCA mutation was demonstrated in less than 10% of Thai ovarian cancer patients. Higher rate of mutation was found in high grade serous cancer.